(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The enrollment system is crucial in proceeding to senior high school. Online processing is now more relevant than the other way of enrollment because of the pandemic in which people were not allowed to go out. In that case, the schools have begun implementing an online process in which students can pass the requirements to the school’s website. The researchers will use descriptive methods to derive the information needed for the system fully. The researchers will use different apps to complete a fully functional enrollment system for Bestlink College of the Philippines students. In the planning phase, the researchers conducted a Google Meet to discuss and brainstorm ideas for creating our Enrollment system. The researchers also researched and found related studies to help them create a new enrollment system before finishing and finalizing the data gathered. For the designing part, the researchers, the programmer, and the system analyst used the best experimental system to try and find the accurate program for the Enrollment system. Furthermore, in the analysis stage, the programmer will coordinate with members like the system analyst and project manager in creating and providing codes for shaping the system. Then, in the testing stage, the researchers will test whether the system’s parts are flexible and functioning. Finally, in the Implementation stage, the researchers will test the system by surveying the selected participants. With the help of the survey, the researchers will surveillance the functions, capability, and usefulness of the Enrollment system. This will also show what actions will resolve the problems encountered. In the maintenance stage, the researchers will check the survey’s feedback, which will help improve the Enrollment system. The problems detected should be easily resolved and reported to the users. Our system will provide the process you will encounter while enrolling in senior high school at Bestlink College of the Philippines. You may start to fill up your information sheet and give the required things that the school is requesting; after that, you can now begin to submit your enrollment form. Enrollment systems are necessary because it is the key to opening the door of education. Without an enrollment system, the school cannot have information about a student.